Influenza vaccination: key facts for general practitioners in Europe-a synthesis by European experts based on national guidelines and best practices in the United Kingdom and the Netherlands - George Kassianos; Patricia Blank; Oana Falup-Pecurariu; Ernest Kuchar; Jan Kyncl; Raul Ortiz De Lejarazu; Aneta Nitsch-Osuch; Gerrit A Van Essen (BioExcel Publishing Ltd, 2016)
Currently there is no influenza vaccination guidance for European general practitioners. Furthermore, although the European Council recommends a target seasonal influenza vaccination rate of 75% in the elderly (65 years and above) and in anyone aged >6 months with a chronic medical condition, there remain wide discrepancies throughout Europe. A harmonised guideline regarding not only vaccination strategy but also for the consistent diagnosis of influenza across Europe is essential to support a common approach for the implementation of seasonal influenza vaccination across Europe. This document is based on pre-existing guidelines available in the UK and Netherlands and has been approved by a group of European experts for use throughout Europe. As well as providing a standardised influenza diagnosis, it also reviews the current recommendations for influenza vaccination, the types of vaccine available, the contraindications, vaccine use in special populations (in pregnancy, children, and in those with egg allergy), and concomitant administration with other vaccines. The effectiveness, safety, and timing of the seasonal influenza vaccine are also reviewed. A second section provides practical guidance for general practitioners for the implementation of a seasonal influenza vaccination program, including the selection and notification of those eligible for vaccination, as well as suggestions for the organisation of a vaccination programme. Finally, suggested responses to common patient misconceptions and frequently asked questions are included. The aim of this article is to harmonise the diagnosis of seasonal influenza and the approach of European general practitioners to seasonal influenza vaccination in order to better identify influenza outbreaks and to move towards reaching the target vaccination rate of 75% throughout Europe.